Analisa Water Hammer Pada Pipa Sirkulasi Condesate Extraction PUMP PT PJB UBJOM PLTU Indramayu - Harun Al Rosyid; Indah Handayasari; Sugeng Tri Hariyanto (Sekolah Tinggi Teknik - PLN, 2015)
System piping network is very important in supporting indramayu production plant with an installed capacity of 3 x 330 MW. Where the water from the condenser flowed into deaerator located on the 3rd floor requires a pump called condesate extraction pump (CEP). Problems arising from design errors and material cause water hammer in the pipes CEP circulation. Water hammer can interfere with the performance of condesat extraction pump (CEP) because it can damage the pump circulation pipe structure with specified intervals. For that this research was conducted in order to minimize the impact of water hammer condesate circulation pipe extraction pump (CEP) by installing gas accumulator. Then will be used as a more detailed analysis of section Enjiniring SO Indramayu power plant turbines in order to make the system more reliable water condesate in operation. The research is focused on solving the problem of water hammer in the pipes condesate circulation extraction pump (CEP). This study was conducted based on a guidebook, P & ID (picture), field surveys and other supporting literature. In order to get the research is real and can be applied in the future.